Electrocochleography-Based Tonotopic Map: I. Place Coding of the Human Cochlea With Hearing Loss - Walia, Amit; Ortmann, Amanda J; Lefler, Shannon; Holden, Timothy A; Puram, Sidharth V; Herzog, Jacques A; Buchman, Craig A (Ear and hearing, 2025)
Due to the challenges of direct in vivo measurements in humans, previous studies of cochlear tonotopy primarily utilized human cadavers and animal models. This study uses cochlear implant electrodes as a tool for intracochlear recordings of acoustically evoked responses to achieve two primary goals: (1) to map the in vivo tonotopy of the human cochlea, and (2) to assess the impact of sound intensity and the creation of an artificial "third window" on this tonotopic map. Fifty patients with hearing loss received cochlear implant electrode arrays. Postimplantation, pure-tone acoustic stimuli (0.25 to 4 kHz) were delivered, and electrophysiological responses were recorded from all 22 electrode contacts. The analysis included fast Fourier transformation to determine the amplitude of the first harmonic, indicative of predominantly outer hair cell activity, and tuning curves to identify the best frequency (BF) electrode. These measures, coupled with postoperative imaging for precise electrode localization, facilitated the construction of an in vivo frequency-position function. The study included a specific examination of 2 patients with auditory neuropathy spectrum disorder (ANSD), with preserved cochlear function as assessed by present distortion-product otoacoustic emissions, to determine the impact of sound intensity on the frequency-position map. In addition, the electrophysiological map was recorded in a patient undergoing a translabyrinthine craniotomy for vestibular schwannoma removal, before and after creating an artificial third window, to explore whether an experimental artifact conducted in cadaveric experiments, as was performed in von Békésy landmark experiments, would produce a shift in the frequency-position map. A significant deviation from the Greenwood model was observed in the electrophysiological frequency-position function, particularly at high-intensity stimulations. In subjects with hearing loss, frequency tuning, and BF location remained consistent across sound intensities. In contrast, ANSD patients exhibited Greenwood-like place coding at low intensities (~40 dB SPL) and a basal shift in BF location at higher intensities (~70 dB SPL or greater). Notably, creating an artificial "third-window" did not alter the frequency-position map. This study successfully maps in vivo tonotopy of human cochleae with hearing loss, demonstrating a near-octave shift from traditional frequency-position maps. In patients with ANSD, representing more typical cochlear function, intermediate intensity levels (~70 to 80 dB SPL) produced results similar to high-intensity stimulation. These findings highlight the influence of stimulus intensity on the cochlear operational point in subjects with hearing loss. This knowledge could enhance cochlear implant programming and improve auditory rehabilitation by more accurately aligning electrode stimulation with natural cochlear responses.